Combining Fused‐Ring and Unfused‐Core Electron Acceptors Enables Efficient Ternary Organic Solar Cells with Enhanced Fill Factor and Broad Compositional Tolerance. Issue 12 (5th September 2019) - Zhan, Lingling; Li, Shuixing; Zhang, Shuhua; Lau, Tsz-Ki; Andersen, Thomas Rieks; Lu, Xinhui; Shi, Minmin; Li, Chang-Zhi; Li, Gang; Chen, Hongzheng
Abstract : The ternary blend strategy has shown great potential to improve the photovoltaic performance of organic solar cells (OSCs). Usually, adopting two acceptors with similar chemical structures shows good compatibility but limited enhancement in performance, whereas adopting two acceptors with different chemical structures always has a compositional sensitivity issue. Herein, a highly efficient ternary OSC with an enhanced fill factor (FF) and a broad compositional tolerance is demonstrated by introducing the fused‐ring acceptor IT‐M to a binary blend based on an unfused‐core acceptor HC‐PCIC and polymer donor PBDB‐TF. Detailed studies on the optical, electrical, and morphological properties of ternary blends reveal the process of charge dynamics and work mechanisms in the ternary device. It is found that the addition of IT‐M into the PBDB‐TF:HC‐PCIC binary blend not only adapts to the parallel‐like model, but also optimizes the morphology and domain sizes in the ternary blend, resulting in a reduced trap‐assisted recombination and suppressed bimolecular recombination. Consequently, open‐circuit voltage ( V oc ), short‐circuit current density ( J sc ), and FF are synergistically enhanced, leading to an improved power conversion efficiency (PCE) of 12.34% with a high V oc of 0.88 V, an increased J sc of 18.69 mA cm −2, and an enhanced FF of 73.82% for the ternary device with 5% IT‐M content. Moreover, the PCEs of ternary OSCs remain above 11% within an IT‐M ratio of 2.5–50%, exhibiting a broad compositional tolerance, which is rarely reported in fullerene‐free ternary OSCs. Abstract : The fused‐ring acceptor IT‐M is added into an unfused‐core acceptor‐based binary blend of PBDB‐TF:HC‐PCIC. Notable fill factor enhancement and a broad compositional tolerance are achieved for the ternary solar cells. Thus, the power conversion efficiency is significantly improved from 11.14% for binary devices to 12.34% for ternary cells.